Adolescent Male Human Papillomavirus Vaccination - Vivian C. Nanagas MD, MSc; Adrienne Stolfi MSPH; Maria T. Nanagas MD; Gregory M. Eberhart MD; Sherman J. Alter MD (SAGE Publishing, 2016)
Objective . To determine male vaccination rates with quadrivalent human papillomavirus vaccine (HPV4) before and after the October 2011 national recommendation to routinely immunize adolescent males. Methods . We reviewed HPV4 dose 1 (HPV4-1) uptake in 292 adolescent males in our urban clinic prior to national recommendations and followed-up for HPV4 series completion rates. After national recommendation, 248 urban clinic and 247 suburban clinic males were reviewed for HPV4-1 uptake. Factors associated with HPV4-1 refusal were determined with multiple logistic regression. Results . Of the initial 292 males, 78% received HPV4-1 and 38% received the 3-dose series. After recommendation, HPV4-1 uptake was 59% and 7% in urban and suburban clinics, respectively. Variables associated with HPV4-1 uptake/refusal included time period, race, type of insurance, and receipt of concurrent vaccines. Conclusions . HPV4-1 vaccination rates in our urban clinic were high before and after routine HPV vaccine recommendations for adolescent males. Our vaccination rates were much higher than in a suburban practice.